Operculum from Erupting Third Molar: An Alternative Donor Site for an Epithelialised-Free Soft-Tissue Autograft - Shah, Harish Kumar; Shrestha, Sanjeev; Sharma, Shivalal; Acharya, Pujan (Journal of Nepalese Society of Periodontology and Oral Implantology, 2019)
Gingival augmentation technique is used to increase the thickness of attached gingiva and arresting the progress of recession. Autogenous epithelialised free gingival graft obtained from palate is a well-established periodontal plastic procedure for root coverage and increasing the width of attached gingiva. This case report shows augmentation of attached gingiva from operculum of erupting third molar as an alternative donor site in marginal tissue recession not extending beyond the mucogingival junction with soft and hard tissue loss interdentally of 31 and 41 in a 20-year-old female.